1998
DOI: 10.2331/fishsci.64.482
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem Biochemical Changes in Muscle of <i>Buccinum striatissimum</i> during Storage

Abstract: The changes in content of ATP and its related compounds, free amino acids, organic acids and opines were investigated in the muscle of B. striatissimum during storage at 0•Ž and 5•Ž. Immediately after shelling, the total amount of ATP and its related compounds were 2.8ƒÊmol/g. ATP, ADP and AMP accounted for 98% of the total ATP and its related compounds. ATP reached the highest level on the 1st day at 0•Ž, then decreased slowly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Immediately after death (0 h of ice-storage) the abdominal cuticles were removed and a piece of the ventral abdominal muscle was cut, as shown in Fig 1, to perform the water-, lowsalt-and high-salt-soluble muscle protein extractions as described below. The extractions were performed on P borealis that had been stored in ice for 5,16,24,48,72,96 and 120 h and on P japonicus and P monodon that had been ice-stored for 16,22,43,71 and 92 h. Eight P borealis, three P japonicus and three P monodon were analysed for each storage period. In addition, the diaphragm, soleus and gastrocnemius muscles of adult rats were used as standards.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immediately after death (0 h of ice-storage) the abdominal cuticles were removed and a piece of the ventral abdominal muscle was cut, as shown in Fig 1, to perform the water-, lowsalt-and high-salt-soluble muscle protein extractions as described below. The extractions were performed on P borealis that had been stored in ice for 5,16,24,48,72,96 and 120 h and on P japonicus and P monodon that had been ice-stored for 16,22,43,71 and 92 h. Eight P borealis, three P japonicus and three P monodon were analysed for each storage period. In addition, the diaphragm, soleus and gastrocnemius muscles of adult rats were used as standards.…”
Section: Methodsmentioning
confidence: 99%
“…
Abstract: Water-, low-salt-and high-salt-soluble protein fractions from the abdominal muscles of Pandalus borealis, Penaeus japonicus and Penaeus monodon extracted immediately after death and after 5,16,24,48, 72, 96 and 120 h (P borealis) or 16, 22, 43, 71 and 92 h (Penaeus spp) of ice-storage were analysed by one-and two-dimensional electrophoresis and immunological techniques. The most evident effect in P borealis was the decrease in the relative amount of myosin heavy chain (MHC) and a concomitant increase in the number and intensity of bands of molecular size about 100 kDa crossreacting with anti-MHC antiserum.
…”
mentioning
confidence: 99%
“…AMP is decomposed to Hx through two pathways in marine invertebrates and thus converted into both IMP and AdR. [11][12][13][14][15] However, Ketut Suwetja et al 16 reported that AdR was not detected during cold storage in the muscles of nine molluscan species including clam and top shell, revealing that AMP is degradated only to IMP in these molluscan species. Table 6 shows the results of the sensory evaluation for cooked samples expressed on a scale of seven from -3 to + 3 using raw samples as a reference.…”
Section: Changes In Atp and Related Compounds During Storagementioning
confidence: 99%
“…B. striatissimum is a marine gastropod that can typically be found in the deep layers of the Japan Sea and just like many edible mollusks, it is a much better source of carotenoids compared with squid meal which one of the reasons that a supplementation of krill meal is necessary in addition to squid meal in the diets of kuruma shrimps (Kantha, ). B. striatissimum is primarily caught and eaten as sashimi in Japan; however, similar species found in other parts of the world continue to be very underutilized (Ban, Ushio, & Yamanaka, ). The intestine portion may be quite useful as dietary source for aquaculture species in future research, however preliminary research on marine snail meat including the muscle and the intestines has been done in the current study to identify any growth‐enhancing effects in these snails.…”
Section: Introductionmentioning
confidence: 99%
“…B. striatissimum is a marine gastropod that can typically be found in the deep layers of the Japan Sea and just like many edible mollusks, it is a much better source of carotenoids compared with squid meal which one of the reasons that a supplementation of krill meal is necessary in addition to squid meal in the diets of kuruma shrimps (Kantha, 1989). B. striatissimum is primarily caught and eaten as sashimi in Japan; however, similar species found in other parts of the world continue to be very underutilized (Ban, Ushio, & Yamanaka, 1998).…”
mentioning
confidence: 99%